Structure-Based Engineering Of An Antiangiogenic Scfv Antibody For Soluble Production In E. Coli Without Loss Of Activity - Denizci Oncu, Melis; Balcioglu, Bertan Koray; Ozgur, Beytullah; Ozturk, Hasan Umit; Serhatli, Muge; Isik, Seyma; Erdag, Berrin; Dinler Doganay, Gizem; Ozdemir Bahadir, Aylin (Aperta, 2021)
Development of monoclonal antibody therapeutics against vascular endothelial growth factor receptor 2 (VEGFR-2) protein, which is the main regulator in angiogenesis, has been a major challenge for years. In the current study, we engineer an inclusion body forming single-chain variable fragment (scFv) against VEGFR-2 by using complementarity determining regions (CDR) grafting technique to improve its solubility and investigate the activity of the engineered molecule. CDR sequences of the target scFv were grafted into the framework of another intrinsically soluble scFv molecule. Based on the computational results, CDR grafting has increased the solubility of the grafted scFv molecule. Results confirmed that the grafting approach increased in vivo folding properties of the target scFv molecule compared with the original scFv molecule. Similar binding affinities to the VEGFR-2 were observed for the original and the grafted scFv by surface plasmon resonance assays. Biological activity assays, including human umbilical vein endothelial cells proliferation and wound healing assays, showed that grafted scFv molecule has an antiangiogenic property. This study suggests that an antiangiogenic scFv fully expressed as an inclusion body can be rescued by grafting its CDR regions to a scFv expressed in a soluble form without any loss in its binding property and its activity.